553 The theory of planned behaviour for drinking and driving: an empirical validation using data collected in two Chinese cities from 2010 to 2014. (1st September 2016) - Li, Qingfeng; He, Huan; Hyder, Adnan A
Abstract : Background: Road traffic crashes are mostly attributable to violations of traffic regulations. Particularly, despite its proven risk, the violation of drinking and driving regulation is still pandemic in many countries and leads to a large number of traffic injuries and fatalities. A better understanding of the factors affecting drinking and driving behaviour is crucial to developing effective interventions to reduce the risk. The most commonly used theoretical model to predict this behaviour is the theory of planned behaviour (TPB). We aimed to assess the ability of this theory in explaining the violation of drinking and driving regulation. Methods: As part of an international road safety consortium, a range of interventions, including social media campaigns, advocacy for legislative change, and law enforcement training, were implemented in two Chinese cities (Suzhou and Dalian) from 2010 to 2014. To monitor and evaluate the project, surveys on motor vehicle's knowledge, attitude and practice (KAP) were regularly conducted from representative samples in both cities. The outcome is whether the respondent has driven a motor vehicle after drinking alcohol in the past 30 days. About 30 indicators measuring drivers' KAP and demographic information were collected. Results: Totally nine rounds of surveys were completed in each city, covering 11, 362 drivers. Overall, about 1.9% of the respondents have driven a motor vehicle after drinking alcohol in the past 30 days. Multivariate logistic regressions show that female drivers are 2.4% (95% CI: −3.4%, −1.5%) less likely to drive after drinking than male drivers. The risk is 1.9% (95% CI: −3.1%, −0.8%) higher among drivers who believe the penaty if caught drinking and driving is heavy than those who believe it is light. The attitude toward drinking and driving and perceived chance of being caught if violated have the largest direct effects. Drivers with correct attitude towards drinking and driving are 27% (95% CI: −28.7%, −25.3%) less likely to do that than drivers who underestimated the risk of drinking and driving. Compared with drivers who believe the chance of being caught is less than 30%, other drivers have a statistically significantly reduced prevalance of drinking and driving. Conclusions: The remarkable consistency between the theory and data indicates that the TPB theory is strongly supported. Social marketing campaign to educate the drivers about the risk of driving and driving, combined with strengthening enforcement to increase the likelihood of being caught if drinking and driving, may be an effective strategy to prevent the violations.